Northanger Abbey [videorecording (DVD)] - Foster, Giles; Firth, Peter, 1953-; Withers, Googie; Hardy, Robert, 1925-2017; Schlesinger, Katharine; Stuart, Cassie; Coy, Jonathan, 1953-; Austen, Jane, 1775-1817 (BBC Video ; Distributed in the USA by Warner Home Video, 2004)
In 18th century Bath, a girl bursting with freshness and passion for macabre Gothic novels experiences intrigue, adventure, and romance, especially when the romantic Henry Tilney invites her to his ancestral home.